2020
DOI: 10.1021/acs.jchemed.9b01020
|View full text |Cite
|
Sign up to set email alerts
|

Reactions: An Innovative and Fun Hybrid Game to Engage the Students Reviewing Organic Reactions in the Classroom

Abstract: A partnership between Brazilian and French professors resulted in the design of a hybrid board game composed of one physical board, a few physical cards, and one application to engage undergraduate students to review the reactions of organic compounds in fun and collaborative ways. It is a multilingual game (English, Portuguese, Spanish, and French) and can be downloaded free-of-charge. Students must get six knowledge jewels to win the game by answering random true or false questions from a database with 600 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The design of specific study materials for distant students has been revealed as a key factor for the success of such a model. Many educators have worked on developing innovative specific tools in the past decade, such as the use of videos, , the web, the creation of real-time experiments, or the development of online games with serious educational objectives. The latest technological developments, such as Virtual Reality (VR) , or Augmented Reality (AR) have emerged as interactive, promising, and engaging tools for chemical education that are adaptable for distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…The design of specific study materials for distant students has been revealed as a key factor for the success of such a model. Many educators have worked on developing innovative specific tools in the past decade, such as the use of videos, , the web, the creation of real-time experiments, or the development of online games with serious educational objectives. The latest technological developments, such as Virtual Reality (VR) , or Augmented Reality (AR) have emerged as interactive, promising, and engaging tools for chemical education that are adaptable for distance learning.…”
Section: Introductionmentioning
confidence: 99%
“…Educators have developed educational games [2][3][4][5] to involve students in interactive and entertaining activities 6 . Games are an excellent method of active learning in a recreative environment 7 and many methods have been tested in the past decade 8 : word game 9 , quiz games [10][11][12][13][14][15][16][17][18] , card games 19,20 , dice games 21,22 , board games [23][24][25][26][27] , computer games [28][29][30] and memory/concentration game [31][32][33] . Surprisingly, the use of videogames to illustrate chemical engineering is relatively unexplored in the literature even though pedagogical videogames exist [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…This enables a careful monitoring of the students' laboratory skills, such as weighing large and tiny quantities, using an advanced microwave hydrothermal process, synthesizing, filtering, and using centrifugation to separate liquid from solid phase, but also of the theoretical skills and knowledge such as understanding the change of water properties at high temperature and pressure, clay structure, the origin of color in indigo, the change of color induced by molecule−host interaction, chemical safety, etc. The student initial knowledge on organic chemistry was also evaluated using a serious game described previously, 30 allowing identification of a weakness problem before starting the organic synthesis, and was used to initiate questions to the instructors. Furthermore, the Genius session has allowed the evaluation the students' ability to transpose an experimental setup to new problems such as changing the molecules integrated in sepiolite, investigating the synthesis parameters and thermochromic or tribochromic materials.…”
Section: Achievement Of Goalsmentioning
confidence: 99%